A study on the clothing shopping practices of selected Japanese women in Metro Manila - Dela Cruz, Nijan Melgar; Escano, Maria Monica R. (2006.)
The objective of this study was to determine the clothing shopping practices of selected single Japanese women in their 20's in Metro Manila. Descriptive research method and normative survey design were used to gather and analyze the data. The questionnaire was the primary data-gathering instrument. Convenience sampling and snowball sampling were used to gather the sample of 32 respondents. The respondents were selected from three universities namely, UP Diliman, De La Salle University Taft, and Ateneo de Manila University. Most of the respondents are 21 and 23 years old and are currently studying in the country. A majority of them have a total of monthly income or allowance of Php 20,0001 to Php 25,000 with a monthly clothing budget of less than Php 5,000. Survey results revealed that most of the respondents have a routine schedule of shopping for clothing monthly, usually on weekends and in the afternoon. Regular department stores are the respondents' most patronized retail establishment. Most of the respondents make generally planned decisions when shopping for clothing. They mostly shop alone or with friends and take control on when and where to shop. The most influential store characteristics affecting the respondents' shopping decisions are goods assortment, location and convenience while magazines and friends are the most influential mass media and interpersonal influences respectively. Most of the respondents can spend Php 301 to Php 500 for a blouse and more than Php 1,000 for a skirt, a pair of slacks/pants, a dress, or for a coat/jacket. Most of them also take advantage of sales and prefer to pay in cash. For the respondents, the color, style, and price were the most important clothing variables, the price being the most satisfactory variable. Factor analysis revealed that the respondents are also practical shoppers and aesthetics is the major consideration to make them satisfied with the clothing they buy.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Consumer behavior